Stop and frisk: the use and abuse of a controversial policing tactic - White, Michael D. (New York University Press, 2016)
Two tales of stop and frisk -- The historical context -- The contemporary legal context -- Crime-control benefits and collateral consequences -- (with Weston Morrow) -- Beyond a few bad apples -- The future of stop and frisk